2020
DOI: 10.24871/192201891-96
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastroesophageal Reflux Disease (GERD) in Dyspepsia Patients in Primary Referral Hospital

Abstract: Background: Gastroesophageal reflux disease (GERD) is caused by reflux of stomach contents into the esophagus and give the typical symptoms as heartburn. The prevalence of GERD was vary around the world. Prevalence of GERD by endoscopy in Jakarta was 22.8%. Limited data exist to determine the prevalence and related factors of gastroesophageal reflux disease (GERD) in the population without alarm symptoms. Validated GERDq questionnaire can be used easily to diagnose GERD in primary health care. This study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
(21 reference statements)
0
6
0
2
Order By: Relevance
“…This is also in line with a study conducted by Darnindro et al, where GERD patients aged 30-39 years (25.5%) are the second-largest GERD sufferers after the age of 50-59 years (29.4%). 5 From the previous studies, it was found that the prevalence of reflux esophagitis increases with age. 5 The incidence of GERD increases because increasing age is a risk factor for a person to experience GERD which is influenced by lifestyle factors, one of which is smoking.…”
Section: Gerd Percentage Based On Agementioning
confidence: 99%
See 1 more Smart Citation
“…This is also in line with a study conducted by Darnindro et al, where GERD patients aged 30-39 years (25.5%) are the second-largest GERD sufferers after the age of 50-59 years (29.4%). 5 From the previous studies, it was found that the prevalence of reflux esophagitis increases with age. 5 The incidence of GERD increases because increasing age is a risk factor for a person to experience GERD which is influenced by lifestyle factors, one of which is smoking.…”
Section: Gerd Percentage Based On Agementioning
confidence: 99%
“…5 From the previous studies, it was found that the prevalence of reflux esophagitis increases with age. 5 The incidence of GERD increases because increasing age is a risk factor for a person to experience GERD which is influenced by lifestyle factors, one of which is smoking. 1 Apart from lifestyle factors, with increasing age there are physiological changes, namely by decreasing the production of bicarbonate of saliva which causes increased exposure to acid reflux in the esophagus due to slow acid clearance.…”
Section: Gerd Percentage Based On Agementioning
confidence: 99%
“…Studi lain dari Darnindro, dkk. 4 menyebutkan bahwa prevalensi GERD lebih tinggi pada wanita, meningkat seiring kenaikan usia dan peningkatan indeks massa tubuh (IMT), serta muncul pada 50% perokok aktif, 33,3% peminun kopi rutin, dan 56,2% dari peminum alkohol aktif. Sedangkan, data epidemiologi di Amerika Serikat menyatakan satu dari lima orang dewasa memiliki keluhan refluks esofagus berupa heartburn dan/atau regurgitasi asam lambung sekali dalam seminggu, dan lebih dari 40% di antaranya mengeluhkan gejala tersebut setidaknya sekali dalam sebulan.…”
Section: Gastroesophagealunclassified
“…Gastroesophageal Reflux Disease (GERD) has a Silvikarina Erfanti Dewi Halim complex pathophysiology in the form of a dysfunctional esophagogastric junction, an antireflux barrier consisting of the LES and crural diaphragm, coupled with impaired esophageal clearance and changes in the integrity of the esophageal mucosa (8). Research conducted at Fatmawati Hospital, Jakarta, in 2021 found that the prevalence of GERD was 49% (9). This condition is caused by many factors, namely environmental factors, diet, and physiology (5).…”
Section: Introductionmentioning
confidence: 99%
“…This condition is caused by many factors, namely environmental factors, diet, and physiology (5). The prevalence of GERD in Asian countries such as Iran ranges from 6.3%-18.3%, Palestine shows a higher rate of 24%, Japan and Taiwan around 13%-15% (9). Unlike the case with East Asia, the prevalence of GERD ranges from 2% -8% (9).…”
Section: Introductionmentioning
confidence: 99%